Scrub typhus in Southern Districts of West Bengal - Nilendu Sarma; Sayantani Chakraborty (Wolters Kluwer Medknow Publications, 2017)
Scrub typhus has been previously reported from north and eastern Indian states and areas such as Kashmir, Himachal Pradesh, Assam, Sikkim, and Darjeeling district of West Bengal. It has also been known to be endemic in some parts of South India (Eastern and Western Ghats). However, no cases have ever been reported from the southern districts of West Bengal. Here, we report five cases of scrub typhus from South 24 Parganas and Kolkata, two districts in the southern part of West Bengal, India.